Plumbing engineering & design handbook of tables (American Society of Plumbing Engineers, 2008)
This book is a comprehensive reference tool that offers in one source volume all the equations, sizing tables and other engineering and design tables used by plumbing engineers, designers and contractors on a daily basis. The book includes applicable tables and information from the major plumbing codes and standards used throughout the U.S. This unique book is a collaborative effort of plumbing engineers and designers. It provides the data and information used every day to engineer, design and install plumbing systems. The handbook, with approximately 2,400 pages of equations and tables, is a working guide and reference for engineers, plumbing system designers, plumbing officials, architects, plant engineers, inspectors, journeymen, students, contractors, builders, and all those associated with the plumbing and contracting industry. It provides data and tables in an easy-to-use and understand format.